PENGARUH BRAND IDENTIFICATION, BRAND EXPERIENCE, DAN BRAND TRUST TERHADAP BRAND EVANGELISM PRODUK SMARTPHONE DIKALANGAN GEN Z DALAM PERSPEKTIF BISNIS ISLAM - Fadila Wahyu Amanda; Yulistia Devi; Citra Etika (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This study is motivated by the increasing use of smartphones among Generation Z, where smartphones function not only as communication tools but also as symbols of identity and lifestyle. This phenomenon encourages the emergence of brand evangelism behavior, which refers to consumers’ willingness to actively recommend and defend the brand they use. The study aims to analyze the influence of brand identification, brand experience, and brand trust on brand evangelism of smartphone products among Generation Z users of Apple iPhone in Bandar Lampung from the perspective of Islamic business. A quantitative approach was employed using a survey method through questionnaires distributed to respondents selected by non probability sampling technique. Data were analyzed using the Partial Least Square model to examine the relationships among variables. The results indicate that brand identification and brand trust have a positive and significant effect on brand evangelism, while brand experience does not have a significant effect. These findings suggest that identity attachment and trust in a brand are the primary factors encouraging consumers to become evangelists, whereas usage experience alone is insufficient without strong emotional attachment and confidence in the brand. From the Islamic business perspective, this behavior aligns with the principle of promoting goodness, provided it is conducted honestly, proportionally, and without harming others